Molecular Detection and Genotyping of Enterocytozoon bieneusi in Racehorses in China - Zhao, Aiyun; Li, Dongfang; Wei, Zilin; Zhang, Ying; Peng, Yushi; Zhu, Yixuan; Qi, Meng; Zhang, Longxian (Frontiers in Microbiology, 2019)
Enterocytozoon bieneusi is a widely distributed human and animal pathogen. However, few data are available on the distribution of E. bieneusi genotypes in racehorses. In this study, 621 fecal specimens were collected from racehorses at 17 equestrian clubs in 15 Chinese cities. E. bieneusi was detected via nested polymerase chain reaction (PCR) amplification of the internal transcribed spacer (ITS) gene. The overall infection rate of E. bieneusi was 4.8% (30/621). Statistically significant differences were found in the prevalence of this parasite among the equestrian clubs (χ2 = 78.464, df = 16, p < 0.01) and age groups (χ2 = 23.686, df = 1, p < 0.01), but no sex bias was found among the racehorses for the E. bieneusi infections (χ2 = 1.407, df = 2, p > 0.05). Ten E. bieneusi genotypes were identified, including seven known genotypes (EbpC, EbpA, Peru6, horse1, horse2, CAF1 and TypeIV) and three novel genotypes (HBH-1, SXH-1 and BJH-1). Phylogenetic analysis showed that EbpC, EbpA, Peru6, horse2, CAF1, TypeIV, BJH-1 and SXH-1 belonged to Group 1 of E. bieneusi, HBH-1 belonged to Group 2, and horse2 belonged to Group 6. Our findings advance the current knowledge of E. bieneusi prevalence and genotypes in racehorses in China.